2018
DOI: 10.1007/s00540-018-2545-1
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine mitigates sevoflurane-induced cell cycle arrest in hippocampus

Abstract: Sevoflurane suppressed neuron cell proliferation via inhibiting the expression of BDNF and TrkB, and DEX relieved the neurotoxicity induced by sevoflurane via α2 adrenergic receptor. These findings provided new evidence that DEX exerted as a neuroprotective strategy in sevoflurane-induced neuro-damage, and provided new basis for the clinical application of DEX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…DEX reduces the neurotoxicity of sevoflurane through many pathways: inhibiting apoptosis and autophagy [59], increasing the expression of tyrosine kinase B (TrkB) and BDNF, promoting neurocyte proliferation, maintaining nervous system function [60], inhibiting neuronal mitochondrial dynamin-related protein (Drp1) [37], and dosedependently activating the bone morphogenetic protein (BMP)/Smad pathway to regulate self-renewal, differentiation, proliferation, migration, and apoptosis of the neuro-cyte [61]. The multiple signal pathways we mentioned above show that DEX has played a significant role in neuroprotection during infant development, laying the foundation for the safe adhibition of DEX in children and pregnant women and solving the problem of general anesthesia drug selection for children.…”
Section: Reduces Neurotoxicity Of Anesthetics and Regulatesmentioning
confidence: 99%
“…DEX reduces the neurotoxicity of sevoflurane through many pathways: inhibiting apoptosis and autophagy [59], increasing the expression of tyrosine kinase B (TrkB) and BDNF, promoting neurocyte proliferation, maintaining nervous system function [60], inhibiting neuronal mitochondrial dynamin-related protein (Drp1) [37], and dosedependently activating the bone morphogenetic protein (BMP)/Smad pathway to regulate self-renewal, differentiation, proliferation, migration, and apoptosis of the neuro-cyte [61]. The multiple signal pathways we mentioned above show that DEX has played a significant role in neuroprotection during infant development, laying the foundation for the safe adhibition of DEX in children and pregnant women and solving the problem of general anesthesia drug selection for children.…”
Section: Reduces Neurotoxicity Of Anesthetics and Regulatesmentioning
confidence: 99%
“…Dexmedetomidine has sedative, analgesic, and sympatholytic properties. Several preclinical studies have suggested that dexmedetomidine provides neuroprotective effects against volatile and intravenous anesthetics in young animal brains 10,11 . Moreover, a few case reports in neonates and young children have described the feasibility of anesthesia with dexmedetomidine‐remifentanil in different clinical scenarios 12‐14 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of this dichotomy, it has become important to identify prospective neuroprotective agents and techniques that could counteract or prevent anesthetic-induced toxicity. These agents may come in the form of mitochondrial fission inhibitors (Xu et al 2016), ROS scavengers (Boscolo et al 2012), caspase activity modulators (Chaparro et al 2013;Inoue et al 2004), AKT/GSK3␤ signaling pathway inhibitors (Tao et al 2016), endoplasmic reticulum stress inhibitors such as salubrinal (Ge et al 2015), or new, neuroprotective anesthetic agents (Alam et al 2017;Bo et al 2018). With the major focus of anesthetic-induced neurotoxicity on the mitochondria, researchers have been looking at ways to mitigate fission activation by targeting Drp1-mitochondrial interaction (Xu et al 2016) and mitochondrial permeability transition pore activation (Chen et al 2015;Lamarche et al 2013).…”
Section: Neuroprotective Strategiesmentioning
confidence: 99%